What drives alignment during text chat with a peer vs. a tutor? Insights from cued interviews and eye-tracking. (July 2019) - Michel, Marije; O'Rourke, Breffni
Abstract: Alignment refers to the largely automatic tendency of interlocutors to re-use each other's language patterns in the course of authentic interaction (Pickering & Garrod, 2004). However, little is known about alignment during L2 interaction, where recycling of a partner's language - in contrast to L1 conversations - might be a more conscious, strategic behaviour (Costa, Pickering & Sorace, 2008). In this paper we explore attention and awareness of L2 speakers to their partner's language use during digitally mediated communication (text chat) and see whether and how they re-use each other's lexical phrases. Twelve English-L1 learners of L2 German participated in a task-based text chat discussion. Participants communicated under two different conditions: with a native speaker tutor vs. with a language learning peer. Three data sources were scrutinised: (1) chatlog analyses looked for re-used lexical phrases; (2) eye-gaze fixations on re-used text served as measures of attention; (3) awareness of language re-use was evaluated by means of cued interviews. Results reveal both unaware and strategic alignment; more of it happening in the tutor chat; and more advanced students being less inclined to copy their partner. Findings will be discussed in light of Costa et al.'s (2008) framework on L2 alignment.